Validation of the Persian Version of the Langer Mindfulness Scale - Moafian, Fatemeh; Pagnini, Francesco; Khoshsima, Hooshang (Frontiers in Psychology, 2017)
This study validates the Persian version of the Langer Mindfulness Scale (LMS). The original scale consists of 21 items and 4 subscales; namely, novelty producing, novelty seeking, engagement and flexibility. In this study, four samples including 2271 individuals in total participated. Confirmatory factor analysis was employed to test the factorial structure of the Persian version. The results verified a two-factor structure including novelty producing and novelty seeking for the scale and the two subscales of engagement and flexibility were omitted due to marginal fit. The questionnaire showed satisfying psychometric properties in terms of reliability. Furthermore, convergent and discriminant validity of the instrument was examined via investigating the relationship between the Persian LMS with the WHOQOL instrument and negative and positive affect scales. The findings revealed a significant positive relationship between the Persian LMS and positive affect, physical health, psychological health and environmental health. No significant correlations were found between the LMS, social relationships and negative affect.